INTERFERENSI FONOLOGIS PENUTUR BAHASA TAE’ DALAM PENGGUNAAN BAHASA INDONESIA DI DESA BASSIANG TIMUR KABUPATEN LUWU - Fauziyah Ramadhani; Arief Fiddienika (Jurnal Bastra (Bahasa dan Sastra), 2024)
Interference is commonly found in communities that use two languages, often referred to as bilingual communities. The contact between two languages, namely the first language and the second language, leads to this phenomenon. Similarly, in regions in Indonesia that have their own regional languages, Luwu Regency also has its regional language, namely the Tae' language, used as the first language, while Indonesian is used as the second language. In the application of these two languages, some individuals are capable of using them according to the language rules, while others may not be proficient in their application. Therefore, this study aims to describe the phonemes in Indonesian that experience interference due to language contact with the Tae' language. This research adopts a qualitative analysis approach. The data collection techniques used are observation and in-depth interviews with informants. The results of the study reveal three phonological interferences, namely addition interference, reduction interference, and substitution interference.